Synthesis and Evaluation of Some New Benzothiazepinylpyridine Derivatives as Anticonvulsant Agents - HEMLATA KAUR; ASHOK KUMAR (International Journal of Pharma and Bio Sciences, 2010)
A simple High Performance Thin Layer Chromatographic (HPTLC) method has been developed for the analysis of santonin in different extracts of Artemisia pallens Wall. The quantification of analytes has been carried out using a mobile phase hexane: ethyl acetate (3:2) on pre-coated aluminium plates (Silica gel Merck 60 F254) and densitometric determination was carried out. The spots were located at 258 nm. The amount of santonin in the extracts has been estimated by comparing the peak area using the standard. Linearity of the standard was found in the concentration range of 1 to 5 µg/spot. The correlation coefficient value was 0.9835. The proposed HPTLC method was found to be simple, faster and reliable for analysis of santonin.